Semiquantitative 2-[18F]FDG PET/CT-based parameters role in lymphoma - Albano, Domenico; Ravanelli, Marco; Durmo, Rexhep; Versari, Annibale; Filice, Angelina; Rizzo, Alessio; Racca, Manuela; Pizzuto, Daniele Antonio; Bertagna, Francesco; Annunziata, Salvatore (Frontiers in Medicine, 2024)
2-deoxy-2-[18F]-fluoro-D-glucose (2-[18F]FDG) positron emission tomography/computed tomography (PET/CT) plays a crucial role in the management of lymphoma in different settings, such as staging disease, assessing response to therapy, predicting prognosis, and planning RT. Beside visual analysis, several semiquantitative parameters were introduced to study lymphoma with promising results. These parameters can represent different disease characteristics, like body composition (such as sarcopenic index), dissemination of disease (Dmax), tumor burden (including metabolic tumor volume) and texture features. All these parameters showed promising results, especially in terms of prognosis (progression free survival and overall survival), but lack of standardization and shared methodology remains a big issue. Advances in PET-based biomarkers are on the horizon, yet their integration into clinical decision-making is currently hindered by methodological limitations that require resolution through confirmatory prospective validation in specific patient groups. This review highlights studies demonstrating the prognostic and predictive value of these semiquantitative parameters in lymphoma, while also discussing their potential applicability in clinical practice.